2017
DOI: 10.21037/qims.2017.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance (MR) neurography for evaluation of peripheral nerves and plexus injuries

Abstract: Traumatic conditions of peripheral nerves and plexus have been classically evaluated by morphological imaging techniques and electrophysiological tests. New magnetic resonance imaging (MRI) studies based on 3D fat-suppressed techniques are providing high accuracy for peripheral nerve injury evaluation from a qualitative point of view. However, these techniques do not provide quantitative information. Diffusion weighted imaging (DWI) and diffusion tensor imaging (DTI) are functional MRI techniques that are able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 80 publications
(79 reference statements)
0
46
0
1
Order By: Relevance
“…Increased signal intensity on fluid‐sensitive MRI images is most commonly seen in the ulnar nerve, being present in up to 60% of healthy persons. Nerve diameters in MRI images are also different in different nerves around the elbow . Because of the limitation of the advanced MRI techniques and the lack of standardization for obtaining more reproducible results, differentiation of small changes between nerves is as difficult as it is in electrophysiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased signal intensity on fluid‐sensitive MRI images is most commonly seen in the ulnar nerve, being present in up to 60% of healthy persons. Nerve diameters in MRI images are also different in different nerves around the elbow . Because of the limitation of the advanced MRI techniques and the lack of standardization for obtaining more reproducible results, differentiation of small changes between nerves is as difficult as it is in electrophysiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, diffusion tensor imaging and nerve signal were used extensively to assess the inner texture of peripheral nerves on MRI. 13,[32][33][34][35][36][37] In addition, MRI allowed the evaluation of the fascicular ratio (FR), that is, the ratio between fascicles and non-fascicular tissue. A study compared the FR changes on MRI between patients with peripheral neuropathies and healthy controls, 24,25 and reported that the FR was significantly increased in patients compared with controls (FR: 76.7 AE 15.1 versus 56 AE 12.3; p < 0.0001 for the semiautomatic interface; and FR: 66.3 AE 17.5 versus 47.8 AE 18.4; p < 0.0001 for the automatic interface).…”
Section: Nerve Echotexture Evaluationmentioning
confidence: 99%
“…Different MRI sequences can give excellent imaging of intra-spinal as well as extra-spinal imaging of plexus. MRI can also give a clue about nerve edema, scarring and neuroma formation [14,26].…”
Section: Computed Tomography Scan and Magnetic Resonance Imagingmentioning
confidence: 99%
“…Van der Juis reported that excessive release of muscle from insertion leads to external rotation contracture and anterior shoulder instability. A subset of patients in their series required secondary internal rotation osteotomy [26,63].…”
Section: Subscapularis Lengthening From Insertionmentioning
confidence: 99%